Relationship between 2000-m rowing ergometer performance times and World Rowing Championships rankings in elite-standard rowers - Mikulic, P.; Smoljanovic, T.; Bojanic, I.; Hannafin, J. A.; Matkovic, B. R. (Journal of Sports Sciences, 2009)
In this study, we evaluated the extent to which 2000-m rowing ergometer performance times predicted final rankings at the World Rowing Championships in a sample of 638 rowers of both sexes and body-mass classifications (i.e. open-category and lightweight rowers). Rowing ergometer performance times were examined using a questionnaire, and in 17 of 23 events they were positively correlated (P = 0.049) with the final rankings at the Championships. The highest correlations were for the ergometer performance times achieved by rowers in lightweight men's single sculls (r = 0.78; P = 0.005), women's single sculls (r = 0.75; P = 0.002), men's single sculls (r = 0.72; P = 0.004), and lightweight men's double sculls (r = 0.72; P < 0.001). We used linear regression to establish regression equations to predict final rankings based on 2000-m rowing ergometer performance times for each event in which there was a correlation greater than r = 0.50. Although correlations in 12 events met this criterion, the large standard errors of the estimate hindered ranking predictions in all of the studied events. Regression equations could be used to determine the most probable 2000-m ergometer performance time for a rower to achieve specific rankings at the World Rowing Championships.